Pelatihan Adzan dan Iqomah Bagi Santri TPQ Roudhotul Qulub dan TPQ Miftakhul Ulum Tambak Lekok Pasuruan - Muhammad Nabil Akmal; Hasmi Nur Bayhaqi; Dewi Sekar Arum; Fayola Issalillah; Mirza Elmy Safira; M. Yusron Maulana El-Yunusi; Mudzakkir Mudzakkir; mir Bandar Abdul Majid; Mila Hariani (Jurnal Kabar Masyarakat, 2024)
The Adzan and Iqomah training at TPQ Roudhotul Qulub and TPQ Miftakhul Ulum Tambak Lekok Pasuruan aims to enhance the skills and understanding of students in performing Adzan and Iqomah. This program adopts the Asset-Based Community Development (ABCD) approach, focusing on empowering students as key community assets. The training method includes observation, identification of students' potentials, and the execution of training sessions over three meetings, covering both theoretical and practical aspects. The results indicate an improvement in students' abilities to perform Adzan and Iqomah, the emergence of local leaders among the students, and an increased awareness of the importance of the younger generation in preserving religious traditions. This training also contributes to the formation of new social structures within the TPQ community, where students actively participate in mosque activities